2002
DOI: 10.4319/lo.2002.47.1.0062
|View full text |Cite
|
Sign up to set email alerts
|

A transplant experiment to identify the factors controlling bacterial abundance, activity, production, and community composition in a eutrophic canyon‐shaped reservoir

Abstract: We performed a transplant experiment in eutrophic Sau reservoir to assess the factors that control bacterial abundance, activity, growth rate, and community composition. Samples from the lacustrine and the riverine ends of the reservoir were incubated in dialysis bags placed in situ and transplanted to the other side of the reservoir and also incubated after 1 m filtration to measure predator effects. The bags were sampled at 12-h intervals to estimate bacterial abundance, whole community activity, activity st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
96
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 39 publications
12
96
1
Order By: Relevance
“…To our knowledge, however, this study is only one of a few that directly demonstrates the effect of microbial composition on functioning in the field while controlling for microbial migration (Allison et al, in press;Gasol et al, 2002). Such experiments would also be useful to investigate further details of the relationship between microbial composition and ecosystem functioning.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…To our knowledge, however, this study is only one of a few that directly demonstrates the effect of microbial composition on functioning in the field while controlling for microbial migration (Allison et al, in press;Gasol et al, 2002). Such experiments would also be useful to investigate further details of the relationship between microbial composition and ecosystem functioning.…”
Section: Discussionmentioning
confidence: 97%
“…However, two limitations with such experiments are that the soil matrix differs along with the microbial community and that the transplanted cores may not fully equilibrate with the surrounding environment. Further, such studies do not usually prevent migration of microorganisms after transplantation (but see Gasol et al, 2002), such that the effect of composition on functioning becomes more ambiguous over time; it is then unclear whether changes in microbial composition over time are because of microbial migration or growth within the soil cores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural lake water contains a large variety of organic compounds (Perdue, 2009) and there is also a large variety in bacterial ability to synthesize enzymes for substrate utilization and biomass production. In mixed batch cultures, bacterial growth follows reproducible trajectories (Ammerman et al, 1984;Tranvik and Höfle, 1987) and maintains similar growth-related functions independently of the source of inoculum (Fuchs et al, 2000;Gasol et al, 2002;Langenheder et al, 2005Langenheder et al, , 2006. This can be explained either by similarly composed communities emerging in those cultures or by differently composed communities maintaining similar functions.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown a low survival of allochthonous bacteria in freshwater mesocosms (e.g., Höfle 1992; Leff et al 1998). In reservoirs, the influence by allochthonous bacteria has been found to be local (Simek et al 2001a;Gasol et al 2002) or low (Dumestre et al 2002). On the other hand, results from a few natural freshwater systems have indicated that allochthonous bacteria can influence the assemblage composition of the bacterioplankton (Lindström 1998(Lindström , 2001Crump et al 2003;Stepanauskas et al 2003).…”
mentioning
confidence: 99%